Verfahren zur Charakterisierung und Modellierung von Lithium-Ionen Zellen - Schmidt, Jan Philipp (Schriften des Instituts für Werkstoffe der Elektrotechnik, Karlsruher Institut für Technologie / Institut für Werkstoffe der Elektrotechnik, 2013)
In this work, novel methods are introduced for characterizing the thermal and electrochemical behavior of lithium ion cells. Based on these methods a modeling approach is introduced which allows for the discreet description of four separate domains (both static and dynamic electrochemical and thermal behaviors). The adaption to a wide variety of electrode materials, scalable accuracy and fully automatable parameterization are made possible by the strict separation of model domains.